Peranan Internal Auditor dalam Menunjang Efetifitas Sistem Pengendalian Intern Penggajian Pada PT. Organ Jaya - Iriyadi, Iriyadi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
The goal of this research is studying and researching if internal control system of payment applied by firm has gone properly and how about the rule of internal auditor in supporting internal control system effectiveness of payment at the firm. The application of internal audit has significant influence to internal control effectiveness at the firm. It was proved when internal supervisor conducted evaluation at general affairs division thatâs responsible to time recording and preparing list of salaries found out false working hours enumeration and fictitious list of workersâ salaries. Keywords : Internal Audit; Internal Control System